THE ANALYSIS OF THE READABILITY AND ACCEPTABILITY OF TRANSLATED CHILDREN STORY BY STUDENTS TRANSLATOR - Dera Septiani (Journal of English Education Program (JEEP), 2016)
This paper reports on the analysis of the readability and acceptability of  translated children story by students translator (a case study at english department in one of the private University in West Java) This study was aimed to finding out translated children story by student translators and to find out how far the reader perceive the translated children story based on it’s readability and acceptability. The criteria of readability and acceptability is measured based on Nababan (2000, p. 165). This study employed qualitative research in which a case study design was adopted to get the data. In collecting the data, the writer used two instruments; content analysis research methodology that used a number of procedures to draw valid conclusions from a book or document and questionnaire enabling the writer to know reader perceive the translated children story based on it’s readability and acceptability. The results of the present study shows that Children's story translated into Bahasa Indonesia by 5 student translators used techniques literal translation, addition, reduction, transposition, calque, and borrowing. However, the dominant techniques used were transposition, ideology used was domestication and the method of translation used was free translation. Meanwhile, readers perceived translated children's story based on it’s acceptability and readability. from the average of the point of acceptability was 2.42, 2.37, 2.63 by raters and the average score for readability was 2.85, 2.65, 2.0 by target readers. This study concludes that reader perceived the translated children story as acceptable and readable, It can be seen from the average of the point of acceptability and readability.